Influence of daily usage times on patients’ compliance during at-home bleaching: a randomized clinical trial - Pavani, Caio César [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Sundfeld, Daniel; Santin, Gabriela Cristina; Machado, Lucas Silveira; Bertoz, André Pinheiro de Magalhães [UNESP]; Schott, Timm Cornelius; Sundfeld, Renato Herman [UNESP] (FapUNIFESP (SciELO), 2023)
The effectiveness of at-home dental bleaching treatments depends on the time that bleaching products are in contact with the teeth surface and, consequently, on the adequate use of associated custom acetate trays. Objective: This randomized single-blinded trial aimed to analyze if the daily usage time of these products influences the patient’s compliance behavior when submitted to monitored at-home dental bleaching. Secondary outcomes were color change and tooth sensitivity. Methodology: Sixty-six volunteers were randomly distributed into three groups (n=22): patients were instructed to use the trays for 2 (G2), 4 (G4), and 8 (G8) hours daily. The daily dental bleaching compliance behavior was measured using a microsensor inserted into the trays. Subjective and objective color evaluation assessments were adopted at baseline (T0), one (T1), two (T2), and three weeks (T3) after the beginning of the bleaching treatment, as well as two weeks after the treatment (T4). Tooth sensitivity was analyzed using the VAS scale, ranging from T1 to T4. Results: G2 showed a greater degree of cooperation than G8 and cooperation was inversely proportional to the recommended usage time. Significantly higher color change was observed in the upper arch for G8 when compared to G2 in subjective analysis, from T1 to T4. There were no statistical differences between the groups in objective analysis. Conclusion: Shorter recommended usage time of the bleaching product may improve the patient's compliance with at-home dental bleaching treatments. However, increased daily usage time may promote better subjective color change. Bleaching sensitivity was more significant in the first week for a longer time of use.
Keywords: Bleaching agents; Carbamide peroxide; Clinical trial; Patient compliance; Tooth bleaching; Treatment adherence and compliance